Timely removal of exogenous cytokinin and the prevention of auxin transport from the shoot to the root affect the regeneration potential of Arabidopsis roots - Bernula Dóra (PLANT CELL TISSUE AND ORGAN CULTURE, 2020)
In vitro regeneration of Arabidopsis from roots is generally achieved via indirect organogenesis. First, transdifferentiation of lateral root primordia to calli is achieved by a balanced auxin-to-cytokinin ratio that is followed by the induction of shoot meristem formation using a high cytokinin level. Here we demonstrate that if the root explants were transferred onto a hormone-free medium after a transient (4-days) cytokinin treatment, embryogenic marker genes (LEC1, LEC2, FUS3) started to be expressed. App. 50% of the regeneration foci developed into plantlets with trichome-less cotyledon-like leaves. Moreover, the somatic embryogenesis defective lec1 mutant could regenerate only shoots with trichome-bearing leaves under this condition. Based on these observations, the mixed accomplishment of shoot organogenesis and somatic embryogenesis is hypothesized in the Arabidopsis root explants cultured under hormone-free conditions following cytokinin induction. Using whole seedlings instead of root explants in the same experimental set up, no regenerates were formed on the roots. Applying the auxin transport inhibitor TIBA to the root-to-shoot junction of the seedlings, the regeneration ability of the root could be restored. The observations indicate that shoot-derived endogenous auxin blocks the cytokinin-induced regeneration process in the roots of whole seedlings. The expression of the wound-induced transcription factor WIND1 could be detected in the roots of unwounded seedlings if the shoot-to-root auxin transport was inhibited. Manipulating the exogenous cytokinin level together with the endogenous shoot-to-root auxin transport therefore could mimic the effect of wounding (removal of shoot) on plant regeneration from roots. Key message Transferring root explants from high cytokinin to hormone-free conditions resulted in the expression of embryogenic markers. Inhibiting the shoot-to-root auxin transport had similar effect on regeneration as wounding.